2021
DOI: 10.1515/med-2021-0364
|View full text |Cite
|
Sign up to set email alerts
|

Research progress of gut microbiota and frailty syndrome

Abstract: Frailty is a clinical syndrome caused by homeostasis imbalance. It is characterized by marked vulnerability to endogenous or exogenous stressors, reduced self-care ability, and increased mortality risk. This aging-related syndrome is common in individuals older than 65 years and carries an increased risk for poor health outcomes. These include falls, incident disability, incapacity, and mortality. In addition, it can result in a poor prognosis for other comorbidities. With the aging population, frailty increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 113 publications
0
7
0
Order By: Relevance
“…As a result, musculoskeletal system disorders and neurodegenerative diseases might develop. All of the above can predispose individuals to frailty [ 50 , 51 ]. Regarding depression, gut microbiota can affect the nervous system through the gut–brain axis, which consists of the immune system, vagus nerve, and neuroendocrine system, all of which can modify and control cognitive functions such as depression [ 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, musculoskeletal system disorders and neurodegenerative diseases might develop. All of the above can predispose individuals to frailty [ 50 , 51 ]. Regarding depression, gut microbiota can affect the nervous system through the gut–brain axis, which consists of the immune system, vagus nerve, and neuroendocrine system, all of which can modify and control cognitive functions such as depression [ 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…All of the above can predispose individuals to frailty [ 50 , 51 ]. Regarding depression, gut microbiota can affect the nervous system through the gut–brain axis, which consists of the immune system, vagus nerve, and neuroendocrine system, all of which can modify and control cognitive functions such as depression [ 51 , 52 ]. Taken together, both of the presented physiological pathways to frailty and depression (i.e., inflammatory markers and microbiota) indicate a bidirectional association between frailty and depression.…”
Section: Discussionmentioning
confidence: 99%
“…Another factor with a recognized impact on the ENS function and structure is the gut microbiota [71]. Besides its influence on postnatal development, experimental depletion of microbiota leads to the degeneration of enteric neurons in adults.…”
Section: Discussionmentioning
confidence: 99%
“…findings also suggested that cirrhotic patients with frailty may be at high risk for receiving invasive treatments, which may be another potential reason for the poor long-term clinical outcomes of these patients [45]. Pathophysiologically, frailty has been related to upregulated inflammatory response, impaired systemic immune dysfunction, and gut microbiota disorder [46][47][48], which may also partly explain the association between frailty and poor TFS in patients with cirrhosis. Studies are warranted to determine the molecular pathways involved.…”
Section: Plos Onementioning
confidence: 99%